China’s Economic Statecraft towards South Asia: Concerns and Prospects - Bhuiyan, Md Ikhtiar Uddin; Siddique, Md. Naim Akter (The Jahangirnagar Review, 2024)
This paper aims to study China’s economic statecraft in South Asia, as it appears to be an integral part of China’s strategy to advance its commercial interests as well as expand its political influence. The study also focuses on economic statecraft, which means the use of economic might for strategic objectives. More specifically, economic statecraft is understood to be a state-market nexus. In addition, the study investigates the institutional arrangements and multilateral mechanisms that China has adopted to achieve its grand strategy. These are major components of Chinese economic diplomacy, or, in other words, using the economy to promote politics. Regarding China’s economic diplomacy, two approaches were also explored. Firstly, Chinese policy is to use diplomacy to achieve economic goals and benefits. Secondly, Chinese policy is to use economic means in pursuit of political objectives. Thus, the study explores China’s growing economic expansion and political influence, which have become important tools in Chinese foreign policy. This leads to addressing one vital question: under what circumstances can China's economic dominance be translated into political dominance, and whether this will result in a new dynamic in the world? Qualitative approach and secondary data used to address the research questions.